STUDENT CENTERED LEARNING IN ENGLISH ALIVE LEARNING THROUGH COMMUNICATIVE APPROACH - Winarsih Winarsih (IJOTL-TL: Indonesian Journal of Language Teaching and Linguistics, 2017)
Student Centered Learning ‘SCL’ approach has major pedagogical benefits to identify and know how the responsibility of SCL puts on learners, for their own learning by using variety of English language actively as medium of instruction to class subjects. It involves students in more decision-making processes, and learns English by doing to class subjects learning. They are 90% doing participating and the real thing during class while students practicing English for real-world skills. Learning becomes more active, it becomes more memorable: because it is personalized, and relevant to the students’ own lives and experiences, it brings English ‘alive’, and makes it relevant to the real world. In the process of learning, the more actively involved students are in their own learning, the more they are likely to remember what they learn. By using communicative approach, English again becomes more ‘real’ and part of the students’ lives.